Effectiveness of lactation counseling on maintenance of breastfeeding - hasan, Rajaa; abbas, Iqbal (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To determine the effectiveness of lactation counseling on maintenance of breastfeeding after cesarean section for study group. Methodology: A quasi-experimental study was conducted on non probability sample (purposive) of (60) women who had cesarean section and sample divided in to two groups (30) of them as a study group from Fatima AlZahra’a Maternity and Pediatric Teaching Hospital & implement lactation counseling on it and another group (30) as control group from Baghdad Teaching Hospital in Baghdad City. Study implemented for the period of April 24th 2011 to August 2nd 2011. A questionnaire was used as a tool of data collection to fulfill with objective of the study and consisted of three parts, including demographic, reproductive characteristics and maintenance of breastfeeding of the sample. A pilot study was carried out to test the reliability of the questionnaire and content validity was carried out through the 11 experts. Descriptive and inferential statistical analyses were used to analyze the data. Results: The results of the study revealed that most mothers their ages within ideal fertility age which ranged between (20-24) years, and most of them had low educational level, and were housewives, and live in urban area, with moderate socioeconomic status, and (53.3%), (50%) respectively of them were primigravida. The study shows that (100%) of the study group had continued breastfeeding, while (76.7%) of the control group had continued breastfeeding and the reasons for discontinuation of breastfeeding for control group are not enough milk and newborn refuse lactation, (73.3%) of the study group had exclusive breastfeeding, while (26%) of the control group had exclusive breastfeeding. Recommendations: The study recommended to reactivate the role of Baby-Friendly Hospitals Initiative in promoting of breastfeeding by implementation of ten steps successful of breastfeeding, and breastfeeding counseling for women during pregnancy and after birth especially who have cesarean section which has important role on maintenance of breastfeeding up to 6 months after birth.